HIGHER IN VIVO SEROTONIN‐1A BINDING IN POSTTRAUMATIC STRESS DISORDER: A PET STUDY WITH [11C]WAY‐100635. Issue 3 (13th February 2013) - Sullivan, Gregory M.; Ogden, R. Todd; Huang, Yung‐yu; Oquendo, Maria A.; Mann, J. John; Parsey, Ramin V.
<x xml:space="preserve">Abstract</x> Background Brain serotonin‐1A receptors (5‐HT1A) are implicated in anxiety. We compared regional brain 5‐HT1A binding in medication‐free participants with posttraumatic stress disorder (PTSD) and healthy volunteers using fully quantitative positron emission tomography (PET) methods. Methods Twenty patients with DSM‐IV PTSD (13 with comorbid major depressive disorder, [MDD]) and 49 healthy volunteers underwent PET imaging with 5‐HT1A antagonist radioligand [C‐11]WAY100635. Arterial blood sampling provided a metabolite‐corrected input function and the concentration of free ligand in plasma (fP) for estimation of regional binding potential, BPF ( = Bavailable / KD). Linear mixed modeling compared BPF between groups across regions of interest (ROIs). Results The PTSD group had higher 5‐HT1A BPF across brain ROIs (P = .0006). Post hoc comparisons showed higher 5‐HT1A BPF in PTSD in all cortical ROIs (26–33%), amygdala (34%), and brainstem raphe nuclei (43%), but not hippocampus. The subgroup of seven PTSD patients without comorbid MDD had higher 5‐HT1A BPF compared with healthy volunteers (P = .03). Conclusions This is the first report of higher brainstem and forebrain 5‐HT1A binding in vivo in PTSD. The finding is independent of MDD. PTSD and MDD have in common an upregulation of 5‐HT1A binding including midbrain autoreceptors that would favor less firing and serotonin release. This abnormality may represent a common biomarker of these stress‐associated brain disorders.